An efficient route to regioselective functionalization of benzo[b]thiophenes via palladium-catalyzed decarboxylative Heck coupling reactions: insights from experiment and computation. Issue 3 (24th November 2015) - Yang, Daoshan; Liu, Yuxia; Sun, Pengfei; Zhang, Ning; Wei, Wei; Sun, Mingyang; Chen, Guang; Bi, Siwei; Wang, Hua
Abstract : This study reports the Pd-catalyzed decarboxylative Heck-type coupling of 3-chlorobenzo[ b ]thiophene-2-carboxylic acids with styrenes. Abstract : Pd-catalyzed decarboxylative Heck-type coupling of 3-chlorobenzo[ b ]thiophene-2-carboxylic acids with styrenes have been developed as an efficient strategy for the construction of functionalized benzo[ b ]thiophenes. Theoretical analysis shows that AgCl generated during the reaction, instead of Pd, π-coordinates with the carboxyl O atom, making easy the rate-determining CO2 dissociation. The divergent reactivities of the Cl-substituted and H-substituted 3-benzo[ b ]thiophene-2-carboxylic acids are mainly due to the presence of the Cl substituent, which reduces the adjacent π–π interplay, thereby significantly contributing to decarboxylation. Therefore, the presence of both AgCl and the Cl substituent are of key importance in ensuring the occurrence of the reaction under the given conditions.